2017
DOI: 10.13181/mji.v26i1.1564
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and behavioral/emotional disorders in primary school-aged children: a cross-sectional study

Abstract: ABSTRAK ABSTRACTBackground: Obesity in children can increase the risks of various chronic diseases. Mental disorders associated with obesity in children include: depression, anxiety, low selfesteem, hyperkinetic disorders, and increased aggressiveness. This relationship is estimated due to vulnerable genetic expressions in obese individuals. This study aimed to find the association between obesity and behavioral/emotional disorder in primary school-aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…2 The incidence is also similar with a previous study in Indonesia that used the same BMI category for children and adolescents from the CDC. 19 However, the prevalence was slightly different from that of another study which used BMI classification from the WHO. 17 Use of the different BMI category between studies has been shown to yield a difference in the prevalence of overweight/obesity.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…2 The incidence is also similar with a previous study in Indonesia that used the same BMI category for children and adolescents from the CDC. 19 However, the prevalence was slightly different from that of another study which used BMI classification from the WHO. 17 Use of the different BMI category between studies has been shown to yield a difference in the prevalence of overweight/obesity.…”
Section: Discussionmentioning
confidence: 56%
“…18 Nevertheless, higher incidence could be found in elementary school (20.4-23.2%). 17,19 High prevalence of overweight and obesity causes Indonesian children to be at high risk of developing hypertension. To our knowledge, there is still a lack of information about elevated BP and its relationship with obesity and anthropometric measures in Indonesia.…”
Section: Significance For Public Healthmentioning
confidence: 99%